Rice Farming Systems in Backward Regions: Socio-economic assessment and sustainable livelihood analysis - Shaik N. Meera,; S. Arun Kumar,; P. Muthuraman,; K. Chiranjeevi,; V. Rajendar Reddy,; Mangat Sain, (Journal of Agricultural Extension Management, 2025)
Evolving a methodology for livelihood mapping at micro level in the vulnerability context helps in preparation of suitable strategies and policy interventions. It is also important to assess different factors associated with and influencing the livelihood options of the weaker and vulnerable sections of the farming community like the scheduled caste/ scheduled tribe (SC/ST) farmers. The present study investigated the livelihoods of SC/ST target population in Kothakota, Wanaparthy and Pebbaire mandals (b locks) of Mahaboobnagar district which is identified as one of the backward regions by the Government of India. This is expected to immensely help in defining the technological interventions and other developmental efforts. For the first time, an effort is made to develop a strong base so that improving the livelihoods could be addressed in a more scientific way rather than focus ing on isolated efforts. The study found that sustainable livelihoods was at the medium level which can be attributed to high social capital and social networks even though human, physical, natural and financial capita ls were not encouraging